Immortality of Consciousness: Phenomenological Consideration - Kąkol, Tomasz (Roczniki Filozoficzne, 2024)
In this article, I defend the phenomenological argument for the immortality of consciousness. In particular, I argue against the possible objections that can be made to the presented argument: from, among others, the alleged facts of unconsciousness, from the distinction between “being” and “phenomenon,” from the distinction between imagining and thinking, from the alleged confusion of the levels of language/thought, from the alleged shocking implications (being God, the denial of elementary scientific knowledge, for example, paleobiology or neuroscience, the lack of explanation of the evil of death).